Rethinking the Position of Islam and Indonesianness Amid Hopes for the Emergence of Multipolar Powers - Baedhowi Baedhowi; Sigit Tri Utomo; Nur Alfi Muanayah (International Journal Ihya' 'Ulum al-Din, 2022)
Globalization in the plurality of cultures and civilizations is a reality that cannot be denied in today's life. It's just that when the power played by the global world has been dominated by unipolar forces. What happens in it is an imbalance in various sectors of life, be it economic, political, socio-cultural, and physical-military. It is this unipolar power that, according to the author, is currently "forcing" the course of capitalistic-secularistic culture and civilization with the support of military power. From this kind of condition, it is necessary to create alternative multipolar energy to create global justice in the political, economic, and socio-cultural fields. In this short introduction, the author tries to reflect on and question our competitive position or our Islamic and Indonesian position during the siege of unipolar forces. This rethinking is a hope for the emergence of real multipolar power so that our position as a nation with the largest Muslim population can become a hope of contribution in offering culture and hope for the emergence of a new global ethic or spirituality for a new world order that is better for all parties.